An analysis of hybrid media practices by selected Malaysian artists - Michael, Valerie; Abd Rahman, Khairul Aidil Azlin; Michael, Vanden; Mohd Razali, Noraziah (Universiti Teknologi MARA, 2023)
Malaysian artists had begun to explore a variety of media and techniques in producing artwork. Through this creative process, the possibility of applying multidisciplinary skills has enhanced the way of producing their concept of hybrid practice through hybrid media. The objective of this paper is to analyse the hybrid media in hybrid art practice among selected Malaysian artists. The methodologies applied in this research were the questionnaires and interviews with selected artists which was highlighting their perceptions about the hybrid media based on their artwork. The researcher distributed questionnaires to 35 selected artists who had experience in producing hybrid artwork. The data was analysed using descriptive analysis and principal component analysis (PCA). The result of the descriptive analysis shows that the experiment, new knowledge, strength, and combination are important elements in hybrid media in the practice of hybrid art. Meanwhile, the result of PCA for the evaluation of hybrid media stated that ideation, media knowledge, and applied collaboration were practised by the selected Malaysian artists. The interview result explained the artists reflection on the result of the questionnaire.